(untitled) (Clinics, 2014)
OBJECTIVE: There is no consensus regarding the most appropriate methods (i.e., the side-by-side versus the stent-in-stent technique) for placing bilateral stents for malignant hilar biliary obstructions. We aimed to perform a quantitative review of the published data regarding the clinical efficacy of the side-by-side and stentinstent bilateral drainage techniques for hilar biliary obstructions. METHODS: A comprehensive search of several databases was conducted and a fixed-effects or random-effects model was used to pool the data from all of the study end-points. RESULTS: Four clinical trials were identified. A comparison of the side-by-side and stent-in-stent groups revealed no significant differences with respect to the rates of successful placement, successful drainage, early complications, late complications and stent occlusions. There were also no significant inter-group differences in stent patency and patient survival and no publication bias was observed. CONCLUSIONS: The performance of the side-by-side technique appears to be similar to that of the stent-instent technique for bilateral drainage in patients with malignant hilar biliary obstructions.